Pengaruh Live Streaming Content, Online Customer Review dan Voucher Discount terhadap Perilaku Impulsive Buying: (Studi pada pengguna aplikasi Shopee di Jakarta Selatan) - Naura Alifia; Yugi Setyarko (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to determine the influence of Live Streaming Content, Online Customer Review and Voucher Discount on the Impulsive Buying Behavior of Shopee Application User in South Jakarta. The population in this study are Shopee application user in South Jakarta. The sample ini this study used a purposive sampling method with the Lemeshow formula and obtained as many as 103 respondents. Data was collected through a questionnaire with a Likert scale spread through a google form, processed using Microsoft Excel 365 and analyzed using SPSS version 29. The results showed that Live Streaming Content and Voucher Discount have a significant effect on Impulsive Buying Behavior while Online Customer Reviews has no affect Impulsive Buying Behavior.